2015
DOI: 10.1111/andr.12069
|View full text |Cite
|
Sign up to set email alerts
|

Benign prostatic enlargement is not associated with diabetes: a population-based study

Abstract: The association between diabetes and benign prostatic hyperplasia remains inconclusive. In this case-control study, we examined the association of diabetes with benign prostatic enlargement (BPE) using the Longitudinal Health Insurance Database 2000 in Taiwan. In total, 20 152 patients with BPE as cases and 20 152 age-matched patients without BPE were included as controls. Conditional logistic regression analyses were performed to calculate the odds ratio (OR) and corresponding 95% CI for having been previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our study also found that the participants with low HDL or increased triglyceride levels had a greater likelihood of LUTS/BPH, which further supports an emerging understanding of the dyslipidemia profile in aging Chinese males. Similar results have also been reported in other studies (37,38). Martin et al's results suggest that HDL cholesterol and lower triglycerides contribute to predicting the improvement of LUTS (37).…”
Section: Observedsupporting
confidence: 87%
“…Our study also found that the participants with low HDL or increased triglyceride levels had a greater likelihood of LUTS/BPH, which further supports an emerging understanding of the dyslipidemia profile in aging Chinese males. Similar results have also been reported in other studies (37,38). Martin et al's results suggest that HDL cholesterol and lower triglycerides contribute to predicting the improvement of LUTS (37).…”
Section: Observedsupporting
confidence: 87%
“…Moreover, various confounding factors such as sleep apnea and medications like diuretics for hypertension may lead to lower urinary tract symptoms [25]. A large population‐based study in an Asian population showed that the significant association between T2DM and BPH was confounded with factors such as hypertension, coronary heart disease, and hyperlipidemia [26]. Among these confounding factors, the clinical studies that included medication adjustments for T2DM were also limited, but metformin in T2DM could affect the prognosis of BPH based on solid evidence from preclinical data [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“… [46] reported that the level of HDL-C was lower, while level of total cholesterol and low density lipoprotein cholesterol (LDL-C) were higher in patients with symptomatic BPH than in controls. In a case-control study performed in Taiwan, China, dyslipidaemia was significantly associated with BPE compared with controls [64] .…”
Section: Biologic Pathophysiology Of Mets and Bphmentioning
confidence: 95%